SCIENCE EDUCATION AND POPULAR EDUCATION: AN INTERVENTION RESEARCH ON CRITICAL ARGUMENTATION IN THE EMANCIPA PROJECT (NATAL/RN) (REMUNOM, 2026)
Popular education views the educational act as political, integrating politicity into daily school life. This study, characterized as qualitative intervention research, aims to investigate how the articulation between Freirean pedagogy and science education impacts the quality of scientific argumentation and the sociopolitical consciousness of students in a popular preparatory course in the periphery of Natal/RN. The experience involved four classes of approximately 30 students each (totaling about 120 subjects) during 2024, with teaching interventions structured in a bi-weekly alternating scheme between groups. The methodology consisted of weekly 7-hour cycles: theoretical foundation, discussion circles on generative themes, weekly text production, and community living. Data were collected through participant observation, field diaries, and analysis of the textual production corpus. The results show that the integration of scientific content and territorial issues fostered the development of critical argumentation, allowing students to transition from generic moral discourses to foundations based on scientific and social evidence. The study concludes that the project impacts life project perspectives and sociopolitical consciousness, despite structural tensions inherent to the performative logic of the ENEM exam.